Colorimetry of Test Pieces and Composite Resin Restorations Subjected to High Temperatures for Forensic Purposes: Standardizing an In Vitro Method (2016)
Objective:To analyze the colorimetric behavior of test pieces and composite resin restorations subjected to high temperatures for forensic purposes. Materials and methods: Invitro pseudo-experimental descriptive study that analyzed the colorimetric changes (cie-1976 L*a*b*) of 75 test pieces and 75 class i occlusal restorations made of composite resin (Z100 3m-espe®), in five colors and subjected to high temperatures. Results: At 200ºC brightness decreased with a tendency to green and a high tendency to yellow. At 400ºC bright-ness decreased with a tendency to red and blue. At 600ºC brightness remained at intermediate values with a tendency to green and a high tendency to yellow. At 800ºC and 1000ºC brightness increased with an absolute tendency to white. There were no significant differences when comparing color coordinates between test pieces and restorations. Conclusions: Test pieces and restorations subjected to high temperatures exhibited color changes that are explained by the properties of brightness, shade and saturation. Experiments in test pieces were validated for the composite resin Z100 3m-espe® as there were no differences between test pieces and restorations. Colorimetric analysis is a practical and inexpensive comparative method of forensic application that can be used to identify the color and type of a composite resin restoration in the case of burned, charred, or calcined human remains.